Predictors of long-term mortality in older patients with hip fractures managed by hemiarthroplasty: a 10-year study based on a population registry in Saxony, Germany - Fakler, Johannes K.M.; Pieroh, Philipp; Höch, Andreas; Roth, Andreas; Kleber, Christian; Löffler, Markus; Heyde, Christoph E.; Zeynalova, Samira (Patient safety in surgery, 2024)
Background Mortality of patients with a femoral neck fracture is high, especially within the first year after surgery, but also remains elevated thereafter. The aim of this study was to identify factors potentially associated with long-term mortality in patients homogeneously treated with hemiarthroplasty for femoral neck fracture. Methods This retrospective cohort study was performed at a single level 1 national trauma center at the university hospital of Leipzig (Saxony, Germany). The study time-window was January 1, 2010 to December 31, 2020. Primary outcome measure was mortality depending on individual patient-related characteristics and perioperative risk factors. Inclusion criteria was a low-energy femoral neck fracture (Garden I-IV) in geriatric patients 60 years of age or older that were primarily treated with bipolar hemiarthroplasty. Date of death or actual residence of patients alive was obtained from the population register of the eastern German state of Saxony, Germany. The outcome was tested using the log-rank test and plotted using Kaplan-Meier curves. Unadjusted and adjusted for other risk factors such as sex and age, hazard ratios were calculated using Cox proportional hazards models and presented with 95% confidence intervals (CI). Results The 458 included patients had a median age of 83 (IQR 77–89) years, 346 (75%) were female and 113 (25%) male patients. Mortality rates after 30 days, 1, 5 and 10 years were 13%, 25%, 60% and 80%, respectively. Multivariate regression analysis revealed age (HR = 1.1; p < 0.001), male gender (HR = 1.6; p < 0.001), ASA-Score 3–4 vs. 1–2 (HR = 1.3; p < 0.001), dementia (HR = 1.9; p < 0.001) and a history of malignancy (HR = 1.6; p = 0.002) as independent predictors for a higher long-term mortality risk. Perioperative factors such as preoperative waiting time, early surgical complications, or experience of the surgeon were not associated with a higher overall mortality. Conclusions In the present study based on data from the population registry from Saxony, Germany the 10-year mortality of older patients above 60 years of age managed with hemiarthroplasty for femoral neck fracture was 80%. Independent risk factors for increased long-term mortality were higher patient age, male gender, severe comorbidity, a history of cancer and in particular dementia. Perioperative factors did not affect long-term mortality.